Literature Study: Implementation of Microlearning in the Digital Era: Studi Literatur: Penerapan Pembelajaran Microlearning di Era Digitalisasi - Kurniawan, Roni; Purnaningsih, Sri (RADIANT: Journal of Applied, Social, and Education Studies, 2025)
This study aims to provide insight and an overview of the application of microlearning in the digital era. The method in this study is descriptive qualitative. The data population used in this study is an indexed journal with the scope of microlearning and digital learning. The data analysis technique uses Miles and Huberman with three stages, including 1) data reduction, 2) data presentation, and 3) drawing conclusions. Microlearning emphasizes the concept of short, practical, and flexible learning. Learning is not limited to the classroom, but can be held digitally by utilizing technological developments. The application of microlearning can be used as an appropriate model in implementing fun and modern digital learning. Microlearning in the digital era can be done in a relatively short time with a scope of core learning topics through the help of interactive media such as podcasts, PowerPoint text, infographics, motion, graphics, and video explainers. Assessments in microlearning can be done with the help of Artificial Intelligence-based applications, including Kahoot, Quizizz, and Moodle. The ability of educators to adapt to technological literacy is the main key to the success of microlearning.